COVID-19 associated mucormycosis: Staging and management recommendations (Report of a multi-disciplinary expert committee) - Hardeep Singh Malhotra; Prashant Gupta; Divya Mehrotra; Himanshu Dandu; Neera Kohli; Veerendra Verma; Apjit Kaur; Neeraj Kumar; Vikas Prabhu; Manish Kumar Singh; Riddhi Jaiswal; Brijesh Mishra; et al. (Journal of Oral Biology and Craniofacial Research)
Even before the onslaught of COVID-19 pandemic could settle, the unprecedented rise in cases with COVID-19 associated mucormycosis pushed the medical health to the fringe. Hyperglycaemia and corticosteroids appear to be the most consistent associations leading to the commonest manifestation of mucormycosis, Rhino-Orbito-Cerebral Mucormycosis. To address challenges right from categorisation and staging of the disease to the management of relentless progression, a multi-disciplinary expert committee was formed to handle the task in an evidence-based format to enforce best practices. The report of the committee on one hand attempts to succinctly present the currently available evidence while at the other also attempts to bridge the evidence-deficient gaps with the specialty-specific virtuosity of experts.